2012
DOI: 10.1002/ptr.3702
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cyanidin‐3‐glucoside Administration Improves Short‐term Spatial Recognition Memory but not Passive Avoidance Learning and Memory in Streptozotocin‐diabetic Rats

Abstract: This research study was conducted to evaluate the efficacy of chronic cyanidin-3-glucoside (C3G) on alleviation of learning and memory deficits in diabetic rats as a result of the observed antidiabetic and antioxidant activity of C3G. Male Wistar rats were divided into control, diabetic, C3G-treated-control and -diabetic groups. The C3G was administered i.p. at a dose of 10 mg/kg on alternate days for eight weeks. For evaluation of learning and memory, initial latency (IL) and step-through latency (STL) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 53 publications
4
17
0
1
Order By: Relevance
“…The present study has shown the reversal of these morphological changes in the pancreas as recorded in other studies with medicinal plants [28] .…”
Section: Treatmentsupporting
confidence: 88%
“…The present study has shown the reversal of these morphological changes in the pancreas as recorded in other studies with medicinal plants [28] .…”
Section: Treatmentsupporting
confidence: 88%
“…Glucose 6-phosphatase increases in the liver facilitating glucose release into the blood. Green tea is considered to be anti-inflammatory, antioxidative, antimutagenic, and anticarcinogenic [33][34][35][36]. Other interesting observation found was the differences in body weight among diabetic and treated groups, diabetic group showed decrease in body weight.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand a gradual significant increase in the body weight was observed in the other treated groups (groups III, IV). This may be due to the retained levels of glucose and insulin levels in green tea and curcumin treated animals [36]. In many previous morphological studies there were many pathological changes, degenerated hepatocytes with polymorphic nuclei, dilated sinusoids and mononuclear cell infiltrate extending through hepatic tissue.…”
Section: Discussionmentioning
confidence: 95%
“…The Y maze used in this study involves no aversive stimuli and was considered suitable for evaluating memory. The specific part of the brain involved in performance of this task includes the hippocampus (Nasri et al, 2012). Since naringenin pretreatment significantly improved spatial working memory in Aβ1-40-injected rats, as evidenced by increase of spontaneous alternation percentage as compared to Aβ-treated rats, this result suggests that naringenin at its used dose improved acquisition of the short-term memory of the Aβ(1-40)-treated rats in Y-maze task.…”
Section: Discussionmentioning
confidence: 83%